Perception of young adults on the use of mobile learning for pre-marital course in Malaysia: A preliminary study - Md Ali, Nurul Amalina; Samsuri, Suhaila; Abu Seman, Muhamad Sadry (Research Associations, 2017)
Mobile learning is a learning method delivered by using mobile devices and technologies. Previous studies indicate that mobile learning has potential to enhance formal as well as informal learning in Islamic marital practices. This study focuses on how young adults perceive the use of mobile devices for pre-marital course. Eighty participants in the pre-marital course held in Malaysia were gathered for the study. A structured questionnaire was distributed to the gathered participants and final results were based on their valid responses. The results indicate that participants' expectations on mobile learning expectations of mobile learning were very high and two-thirds of them were interested to learn more about Islamic marital practices through mobile learning. Based on the results, a few pedagogical recommendations have been made for the relevant authorities.